Use of preprint peer review to educate and enculturate science undergraduates. Issue 3 (27th July 2022) - McDowell, Gary S.; Fankhauser, Sarah; Saderi, Daniela; Balgopal, Meena; Lijek, Rebeccah S.
Key points: Undergraduate science education should include education in scholarly practices like peer review. Authentic experiences in peer review increase science literacy and science identity. Peer review of preprints provides a means for undergraduates to be involved in peer review that is independent of journal gatekeeping processes.